Implementasi Self-Determination Theory dalam Pendidikan Kewirausahaan Sebagai Respon Terhadap Kebutuhan Psikologis Generasi Z (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to identify the characteristics of Generation Z and analyze the appropriate theoretical approaches in entrepreneurship education while still considering the psychological needs of this generation. The research was conducted qualitatively using a literature review method. Analysis was carried out through the study of various literature from 1985 to 2025, as well as utilizing secondary data from the Central Statistics Agency (BPS) and various survey results from other research institutions. The background of this research is based on the still high number of educated labor force that has not been absorbed into the workforce. Research results show that Generation Z has unique characteristics, namely a high preference for flexibility in working, both in terms of time and work location. In addition, Generation Z also has a strong tendency towards the need for autonomy, competence, and relatedness, as well as considering the balance between life and work (work-life balance). The implementation of SDT in entrepreneurial education can be carried out through providing autonomy in choosing and determining business ideas, offering measurable technical skills, and forming teamwork in completing business projects to strengthen social connection. The application of SDT in entrepreneurial education is expected to produce Generation Z that is adaptive, independent, reliable, and has critical thinking skills in decision-making.